2001
DOI: 10.1086/316939
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of the Entire PKD1 Gene: Genetic and Diagnostic Implications

Abstract: Mutation screening of the major autosomal dominant polycystic kidney disease (ADPKD) locus, PKD1, has proved difficult because of the large transcript and complex reiterated gene region. We have developed methods, employing long polymerase chain reaction (PCR) and specific reverse transcription-PCR, to amplify all of the PKD1 coding area. The gene was screened for mutations in 131 unrelated patients with ADPKD, using the protein-truncation test and direct sequencing. Mutations were identified in 57 families, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(168 citation statements)
references
References 66 publications
4
162
1
1
Order By: Relevance
“…5,6 In this study we demonstrate that WGS is a reliable, minimally labour-intensive and reproducible technique with which to overcome the challenge of pseudogene homology and thus make a molecular diagnosis of ADPKD. Using this technique we were able to make a molecular diagnosis in 86% of patients.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…5,6 In this study we demonstrate that WGS is a reliable, minimally labour-intensive and reproducible technique with which to overcome the challenge of pseudogene homology and thus make a molecular diagnosis of ADPKD. Using this technique we were able to make a molecular diagnosis in 86% of patients.…”
Section: Discussionmentioning
confidence: 71%
“…To date, long-range PCR (LR-PCR) amplification, followed by Sanger sequencing, has been the gold standard used by most diagnostic laboratories. 1,5,6 This technique has a diagnostic rate of approximately 90% in well-phenotyped trial cohorts and 40-60% in the commercial reference laboratory. [7][8][9] The technique is labour intensive and thus expensive.…”
Section: Introductionmentioning
confidence: 99%
“…29,34,38 De novo mutations reported by several groups confirm this hypothesis. 24,25,39 The great rarity of some mutations and their confinement within certain families suggests also that they must have occurred very recently. In many cases multiple polymorphisms have been detected on same alleles, being in linkage disequilibrium.…”
Section: Polymorphismsmentioning
confidence: 99%
“…Mutation analysis of the PKD1 gene has been complicated because at least three PKD1-like homologous genes exist on chromosome 16p13.1. Several improved strategies have been developed to detect mutations in the entire PKD1 gene including the duplicated region (Peral et al 1997;Roelfsema et al 1997;Watnick et al 1997; Thomas et al 1999;Rossetti et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These mutations resulted in various alterations of amino acids by substitution, deletion, or insertion of nucleotides (nt). Previous reports suggested that new mutations of the PKD1 gene occur at a significant rate (Peral et al 1997;Rossetti et al 2001). Approximately 80% of the mutations in the 3ЈPKD1 unique region (exons 34-46) were predicted to truncate the protein, and 37% of mutations in the 5Јpart of the gene were missense mutations (Bogdanova et al 2000).…”
Section: Introductionmentioning
confidence: 99%